2011
DOI: 10.1001/archinternmed.2011.306
|View full text |Cite
|
Sign up to set email alerts
|

Cranberries vs Antibiotics to Prevent Urinary Tract Infections

Abstract: isrctn.org Identifier: ISRCTN50717094.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
38
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 138 publications
(42 citation statements)
references
References 30 publications
1
38
0
1
Order By: Relevance
“…E. faecalis was found to be the most common in men and in patients aged over 60. However, women are equally prone to E. faecalis bacteriuria, according to Beerepoot et al [10,19]. They found that 16.5 % of urine samples from asymptomatic patients and 5.4 % of samples from symptomatic patients contained E. faecalis.…”
Section: Discussionmentioning
confidence: 99%
“…E. faecalis was found to be the most common in men and in patients aged over 60. However, women are equally prone to E. faecalis bacteriuria, according to Beerepoot et al [10,19]. They found that 16.5 % of urine samples from asymptomatic patients and 5.4 % of samples from symptomatic patients contained E. faecalis.…”
Section: Discussionmentioning
confidence: 99%
“…In randomised trials comparing continuous co-trimoxazole (480mg daily) with cranberry extract12 and lactobacillus,13 resistance to co-trimoxazole, trimethoprim and amoxicillin in faeces and urine (measured by testing antibacterial sensitivity in the laboratory) had increased after 1 month of antibacterial use (from around 21–28% to around 73–91% in one trial;12 and from around 20–40% to around 80–95% in the other) 13. After 12 months' prophylactic therapy, resistance rates for ciprofloxacin and norfloxacin in urinary Escherichia coli isolates had also increased.…”
Section: Preventing Recurrent Infectionsmentioning
confidence: 99%
“…A more recent double-blind, double-dummy randomised placebo-controlled trial (involving 221 premenopausal women with recurrent UTIs) found that co-trimoxazole (480mg daily) was more effective than cranberry capsules (500mg twice daily) in preventing recurrent UTIs 12. After 12 months, the mean number of clinical recurrences was 1.8 (95% CI 0.8 to 2.7) with co-trimoxazole vs. 4.0 (95% CI 2.3 to 5.6) with cranberry, p = 0.02.…”
Section: Preventing Recurrent Infectionsmentioning
confidence: 99%
“…In recent years Urinary tract infections are developing & are the second most common infection in the world [8]. Men are less than women involved to urinary tract infections, because; men have bigger urethra in their body [9]. UTI is a disease which, created in the woman or man and can transmitted it together (Venereal disease) [10].…”
Section: Introductionmentioning
confidence: 99%